In Gesundheit und Krankheit?: Der Zusammenhang zwischen dem Gesundheitszustand und der Ehestabilität = In health and disease? : The relationship between health and marital stability - Rapp, Ingmar (Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2012)
This Study examines the relationship between health status and the risk of marital separation. The data base is the German Socio-Economic Panel, a representative longitudinal study of private households in Germany. Controlling for marital duration and other covariates, both poor health of one partner and poor health of both partners are associated with a higher risk of dissolution. The results suggest that the higher risk of dissolution is partly caused by financial burdens which are associated with illness. Further possible explanations—social expectations addressed to the healthy partner, an increasing dependence of the sick partner on his spouse, a reduction of alternatives and a deterioration of the marriage match—are of minor importance for the risk of separation. The results are also relevant for explaining health inequalities. They suggest that better health of married people compared to unmarried people not only depends on a protective effect of marriage on health, but is also due to the fact that healthier people are more likely to stay married.